Identification of Novel Variants in Cleft Palate-Associated Genes in Brazilian Patients With Non-syndromic Cleft Palate Only - Machado, Renato Assis; Martelli-Junior, Hercílio; Reis, Silvia Regina de Almeida; Küchler, Erika Calvano; Scariot, Rafaela; das Neves, Lucimara Teixeira; Coletta, Ricardo D. (Frontiers in Cell and Developmental Biology, 2021)
The identification of genetic risk factors for nonsyndromic oral clefts is of great importance for better understanding the biological processes related to this heterogeneous and complex group of diseases. Herein we applied whole exome sequencing to identify potential variants related to nonsyndromic cleft palate only (NSCPO) in the multiethnic Brazilian population. Thirty NSCPO samples and 30 gender- and genetic ancestry-matched healthy controls were pooled (3 pools with 10 samples for each group) and subjected to whole exome sequencing. After filtering, the functional affects, individually and through interactions, of the selected variants and genes were assessed by bioinformatic analyses. As a group, 399 variants in 216 genes related to palatogenesis/cleft palate, corresponding to 6.43%, were exclusively identified in the NSCPO pools. Among those genes are 99 associated with syndromes displaying cleft palate in their clinical spectrum and 92 previously related to cleft lip-palate. The most significantly biological processes and pathways overrepresented in the NSCPO-identified genes were associated with the folic acid metabolism, highlighting the interaction between LRP6 and MTR that interconnect 2 large networks. This study yields novel data on characterization of specific variants and complex processes and pathways related to NSCPO, including many variants in genes of the folate/homocysteine pathway, and confirms that variants in genes related to syndromic cleft palate and cleft lip-palate may cause NSCPO.